THE COMPETENCY BASED APPROACH IN PROFESSIONAL EDUCATION, OR IN CONTRADICTION WITH LABOR SCIENCE - V. Serov (Publishing House of the State University of Management, 2019)
The content and existing practice, the approach and provisions adopted in official methodological documents for assessing the qualifications of personnel, as well as the content and parameters of qualification requirements for employees during their certification have been considered. In light of this and in the light of the ongoing work on the development of professional standards in all sectors of production and the economy, the competency-based approach implemented by the Ministry of Science and Higher Education of the Russian Federation in higher professional education has been analyzed. As a result of this analysis, the shortcomings of conceptual provisions and an approach to assessing the level of professional preparedness of university graduates, to determining and accepting the general economic and professional competencies of graduates of the bachelor and master level have been revealed. Suggestions have been made for adjusting the content of the methodological support of the educational process in terms of assessing knowledge and preparedness for the practical work of graduates of vocational education institutions.